2012 IEEE Wireless Communications and Networking Conference Workshops (WCNCW) 2012
DOI: 10.1109/wcncw.2012.6215501
|View full text |Cite
|
Sign up to set email alerts
|

Using “predictor antennas” for long-range prediction of fast fading for moving relays

Abstract: Notice: Changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published source. Please note that access to the published version might require a subscription. Chalmers Publication Library (CPL) offers the possibility of retrieving research publications produced at Chalmers University of Technology. It covers all types of publications: articles, dissertations, licentiate theses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 8 publications
2
76
0
Order By: Relevance
“…However, for still longer prediction distances in space, the performance starts to deteriorate and the gains of using coherent joint transmission vanish [10]. A specialized 'predictor antenna' system for vehicles has recently been proposed to obtain accurate CSI also at very high velocities [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, for still longer prediction distances in space, the performance starts to deteriorate and the gains of using coherent joint transmission vanish [10]. A specialized 'predictor antenna' system for vehicles has recently been proposed to obtain accurate CSI also at very high velocities [49].…”
Section: Discussionmentioning
confidence: 99%
“…Note that accurate channel estimation can be obtained for high-speed train communications thanks to the use of the predictor antennas concept [29]- [31]. A predictor antenna is placed on the top of the train followed by one or several separate receive antennas.…”
Section: Channel Modelmentioning
confidence: 99%
“…We assume that accurate channel state information can be available at the transmitters, even at high-speeds, using for example the predictor antenna method described in [29]. The resource allocation algorithms proposed in Section III are applied in both access and bakchaul links using the parameters summarized in Table I.…”
Section: A Simulation Parametersmentioning
confidence: 99%
“…6 The scenario with an antenna or antenna array on the roof of a fast-moving bus or tram provides an opportunity as well as a challenge. One innovation is the use of a "predictor antenna" [15]. The vehicle velocity and direction would be relatively constant over the required 5 ms prediction horizon.…”
Section: Challenges and Open Issuesmentioning
confidence: 99%
“…We would avoid the need to extrapolate in time from the measurements. Preliminary results based on measurement campaigns done in a 20 MHz orthogonal frequency-division multiplexing (OFDM) system in 2.68 GHz downlinks showed that using a predictor antenna can significantly improve the CSI feedback accuracy at a vehicular velocity [15]. A maximal normalized correlation above 0.95 was reported between the signal from the predictor antenna and the signal from the antenna behind it mounted on the vehicle roof, with antenna distances (prediction horizons) of up to three wavelengths, in both LOS and non-LOS (NLOS) conditions.…”
Section: Challenges and Open Issuesmentioning
confidence: 99%